Legal Problems of Limitation and Regulation of International Cyber-attack - Shinkaretkaia, G. (Bulletin of Yerevan University C: Jurisprudence, 2018)
Quite recently a new problem – cyber-security issue emerged in international law. The problem refers to finding methods to resist hostile cyber-attacks and to remove their negative impact over critical cyber-infrastructures. The article demonstrates some peculiarities of the use and restraint of cyberattacks which prevent applicability of rules of general international law as well as international humanitarian law and international human rights law. The author concludes that a new special international treaty of a complex character is needed.
Keywords: cyber-security, cyber-infrastructures, computersystems, international humanitarian law, human rights, soft law